POTENSI ABU KERTAS FOOD GRADE SEBAGAI ALTERNATIF FILLER CAMPURAN ASPAL PANAS PENGUJIAN FISIK DAN KIMIA - Amar Ardiansyah; Rizkiardi, Aditiya; Hartatik, Nurani; Prasetyo, Yudi D; Punarta, I Gede Agus (Jurnal Teknik Sipil dan Arsitektur, 2025)
Population growth and industrial activities in Indonesia significantly increase the production of solid waste every year. One of the large amounts of waste that has not been optimally utilized is paper waste, including food grade paper waste. Handling food grade paper waste is an environmental challenge that requires innovative solutions. This research examines the potential of food grade paper ash as an alternative filler in hot mix asphalt through physical and chemical analysis. Food grade paper waste from industries in East Java was burned to ash and tested to meet the technical requirements of asphalt filler. Physical testing included particle size analysis with a No. 200 sieve and specific gravity measurement, while chemical testing used the X-Ray Fluorescence (XRF) method to determine the composition of the main compounds. The test results showed that 85.43% of the ash particles passed the No. 200 sieve, exceeding the minimum limit of 75% according to the 2018 Bina Marga General Specifications. The specific gravity of paper ash was 2.640 gr/cm3, in accordance with the SNI 1970-2008 standard which requires a minimum of 2.5 gr/cm3. The chemical composition of ash is dominated by calcium oxide (CaO) at 71.52%, silica (SiO?) 11.6%, and aluminum oxide (Al?O?) 7.3%, which play a role in increasing the adhesion and stability of asphalt mixtures. With these characteristics, food grade paper ash is suitable to be used as a filler to replace conventional materials in hot asphalt mixtures. The utilization of food grade paper ash not only meets the technical aspects, but also contributes to the reduction of industrial waste and provides an environmentally friendly solution in road construction. Keyword: Food grade paper ash, Filler material, waste utilization, Hot mix asphalt